2016
DOI: 10.1080/10810730.2016.1193916
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Literacy on Surgical Outcomes Following Radical Cystectomy

Abstract: Health literacy is the ability to obtain, comprehend and act on medical information and is an independent predictor of health outcomes in patients with chronic health conditions. However, there is little reported regarding the potential association of health literacy and surgical outcomes. We hypothesized that patient complications after radical cystectomy (RC) are associated with health literacy. In a sample of 368 patients, we found that higher health literacy scores (as determined by the Brief Health Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 25 publications
2
50
1
Order By: Relevance
“…). Of the 44 full‐text articles reviewed, 17 met the inclusion criteria by addressing the relation of HL with various self‐management behaviors in cancer (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Of the 44 full‐text articles reviewed, 17 met the inclusion criteria by addressing the relation of HL with various self‐management behaviors in cancer (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies, 14 were observational; 12 of these studies used a cross‐sectional design, and 2 were longitudinal cohort studies . Three studies used experimental designs: 1 study was quasi‐experimental with 3 arms, and the other 2 studies were randomized controlled trials …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Department of Health and Human Services, 2010). Health literacy has been found to impact health status (Hoover et al, 2015; Sentell, Baker, Onaka, & Braun, 2011), medical decision-making (Wang et al, 2014), access to care (Levy & Janke, 2016), completion of positive health behaviors such as cancer screening (Fernandez, Larson, & Zikmund-Fisher, 2016; Heberer et al, 2016), and health outcomes (Scarpato et al, 2016). For example, individuals with inadequate self-reported health literacy have been found less likely to be adherent to mammography guidelines and to report regular moderate physical activity than those with adequate self-reported health literacy (Fernandez, Larson, & Zikmund-Fisher, 2016).…”
mentioning
confidence: 99%
“…Examples include navigating a questionnaire, medication instructions, or comprehension of diagnosis (Institute of Medicine, 2004). Since the 1960s, research has demonstrated that low health literacy interferes with an individual's ability to manage diseases such as diabetes (Schillinger et al, 2002) and heart failure (Friel, 2016) and can predict negative surgical outcomes (Scarpato et al, 2016). Moreover, health literacy has been cited as the single greatest predictor of an individual's health status (Baker et al, 2007), and it is an indicator of increased hospital visits, morbidity, mortality, and high health care costs (Baker et al, 2002;Institute of Medicine, 2004;Schillinger et al, 2002;Wolf, Gazmararian, & Baker, 2005).…”
Section: Results: Readability Calculations Agreed With Previous Studimentioning
confidence: 99%